Dental prosthetic status and treatment needs of green marble mine laborers, Udaipur, India - Santhosh Kumar; Jyothi Tadakamadla; Harish Tibdewal; D Prabu; Suhas Kulkarni (Wolters Kluwer Medknow Publications, 2011)
Background: Assessment of prosthetic needs in a special population would aid in planning the oral health service programs. The aim of this study was to assess the dental prosthetic status and prosthetic needs in a sample of green marble mine laborers of Udaipur, India. Methods: The study population comprised of 513 green marble mine laborers who were divided into four age groups (15-24, 25-34, 35-44 and 45-54). Prosthetic status and treatment needs along with dentition status were recorded using WHO oral health assessment form. The examination was done by two examiners who were calibrated for inter examiner variability with kappa statistic of 86%. Chi-square test was used to compare the proportions. The significance level was set at α= 0.05. Results: Mean number of missing teeth due to any reason for the whole sample was 0.82. Approximately, 96.5% of the subjects were free from any kind of prosthesis and only the rest of sample (3.5%) had single fixed prosthesis. The overall prosthetic treatment needs was 15.5%. Prosthetic needs increased as the age increased with the age group 45-54 showing the greatest. Prosthetic needs in the lower arch were found to be greater than that of the upper arch. Single unit prosthesis comprised a greater percentage of the whole prosthetic needs (41%). Conclusion: Most of the prosthetic needs of the study population were unmet. The prosthetic needs being four and half-fold greater than the status.